Pseudomonas aeruginosa Resistance in Southeast Asia - Ciptaningtyas, Vincentia Rizke; Lestari, Endang Sri; Wahyono, Hendro (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2019)
INTRODUCTION: The increasing number of multidrug-resistant Pseudomonas aeruginosa worldwide need to be continuously monitored to prevent its transmission. This study reviewed multidrug-resistant Pseudomonas aeruginosa in Southeast Asia.METHODS: Pubmed database was searched (January 2013-March 2018) for relevant articles using specific names of all eleven Southeast Asian countries. The articles retrieved were screened and analyzed to meet the inclusion criteria.RESULTS: A total of 17 articles met the inclusion criteria. Vietnam had the most published data included in this study, East Timor, Cambodia, and Laos had none. There are variations among Pseudomonas aeruginosa resistance in Southeast Asia. Thailand had complete data on antibiotic resistance and had the highest resistance rate of almost all antibiotics. Colistin had the lowest resistance rate among all antibiotics.CONCLUSIONS: Colistin had the lowest resistance rate among all antibiotics. Another study with more extensive data should be done to validate this study. Future research should be explicitly providing detail data results for antimicrobial resistance analyses.